2014
DOI: 10.1038/ncomms4339
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study reveals two new risk loci for bipolar disorder

Abstract: Bipolar disorder (BD) is a common and highly heritable mental illness and genome-wide association studies (GWAS) have robustly identified the first common genetic variants involved in disease aetiology. The data also provide strong evidence for the presence of multiple additional risk loci, each contributing a relatively small effect to BD susceptibility. Large samples are necessary to detect these risk loci. Here we present results from the largest BD GWAS to date by investigating 2.3 million single-nucleotid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
264
3
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 304 publications
(277 citation statements)
references
References 60 publications
7
264
3
1
Order By: Relevance
“…This finding has been replicated in many (if not all) GWASs of bipolar disorder (3)(4)(5). The ANK3 locus is also found to be associated, to a lesser extent, with schizophrenia (6,7).…”
supporting
confidence: 51%
“…This finding has been replicated in many (if not all) GWASs of bipolar disorder (3)(4)(5). The ANK3 locus is also found to be associated, to a lesser extent, with schizophrenia (6,7).…”
supporting
confidence: 51%
“…Large scale collaborative genome‐wide association studies (GWAS) have identified a number of risk loci significantly associated with bipolar disorder (BP), including ODZ4 [Sklar et al, 2011; Muhleisen et al, 2014], CACNA1C [Ferreira et al, 2008; Sklar et al, 2008], ANK3 [Ferreira et al, 2008; Schulze et al, 2009; Muhleisen et al, 2014], NCAN [Cichon et al, 2011], C15ORF53 [Ferreira et al, 2008], and DGKH [Baum et al, 2008a,2008b]. Individually, each of those genes/loci contributes only a small fraction toward overall disease risk, typically <1% of the phenotypic variance [Ferreira et al, 2008].…”
Section: Introductionmentioning
confidence: 99%
“…To date, GWAS approaches have identified 18 loci contributing to the risk of MDD [20,24,59] and over 8 loci associated with BPD [55,63,84,92,106], including shared genetic loci located in the CACNA1C, CACNB2, AS3MT, ITIH3, and CCDC68 genes [22]. An extension of the GWAS approaches such as polygenic score analysis [87], bivariate restricted maximum likelihood (REML) in genome-wide complex trait analysis (GCTA) [21] and linkage disequilibrium (LD) score regression have strongly suggested that mood disorders are polygenic in nature, in that multiple genetic variants interacting with environmental factors contribute to the development of the diseases [87].…”
Section: Introductionmentioning
confidence: 99%
“…Candidate gene and genome-wide association studies (GWASs) have identified a list of candidate genes for MDD [20,24,35,59] and BPD [55,84,92,106]. To date, GWAS approaches have identified 18 loci contributing to the risk of MDD [20,24,59] and over 8 loci associated with BPD [55,63,84,92,106], including shared genetic loci located in the CACNA1C, CACNB2, AS3MT, ITIH3, and CCDC68 genes [22].…”
Section: Introductionmentioning
confidence: 99%